Transcerebellar Diameter: an effective tool in estimating gestational age - Veena Kumari, Memoona Rehman, Erum Majid, Bader Faiyaz Zuberi, Saira Nazeer, Saba Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Estimating correct gestational age is the first and foremost goal of obstetrician and gynaecologist and cannot be underestimated. Commonly the parameters used are BPD, head circumference (HC), Femur length (FL), Abdominal circumference (AC). Recently transverse cerebellar diameter is a new diagnostic tool to measure the gestational age. Aim: To determine the accuracy of transverse cerebellar diameters in estimating gestational age, taking LMP as the gold standard. Study design: Descriptive Cross-Sectional Study. Setting: This study was conducted at Department of Obstetrics & Gynaecology, JPMC, Karachi, Pakistan Duration: Six months after the approval of synopsis from January 29 2021 to 28 July 2021. Methods: Ultrasonographic measurement of Transverse Cerebellar Diameter(TCD) was taken. Routine measurements of crown-rump length or bi-parietal diameter were also done. Accuracy was considered if the difference between TCD and LMP was ≤2 mm. Correlation of age on LMP with TCD was tested using Kendall’s tau-b test and its scatter plot as generated. All the collected data was entered into a proforma attached at the end and used electronically for research purposes. Results: A total of 114 patients were inducted after informed consent. Their mean age was 28.18±27.24 years. Maternal age was 28.18 ±27.24 years, maternal weight was 60.59 ±9.64 kg and BMI was 23.58±3.63 kg/m2.Median (IQR) of gravida was 2.0 (2). Mean of gestational age on LMP was 33.84 ±5.29 and was significantly more as measured by TCD was 31.51±5.05 (p<.001). Age on LPM and TCD showed linear correlation. Accuracy of TCD was documented in 108 (94.7%). Conclusion: It is to be concluded that transverse cerebellar diameter was found to be equally good and relatively comparable with LMP in predicting gestational age.